Instrumental aspects of play at work in information technology organisations. Issue 6 (2nd November 2021) - Chughtai, Hameed
ABSTRACT: Conventional wisdom suggests that play is the antithesis of work. But in the information technology (IT) industry, companies such as Google, Facebook and Microsoft have positively integrated play into the workplace. In an era when the digital is ubiquitous and where play with IT has become commonplace, exploring the nature of play at work could shed light on the broader question of how humans exist in the world. This is an essential question for contemporary Information Systems scholarship. Drawing on the critical hermeneutics of Hans-Georg Gadamer, I offer a narrative account of the instrumental aspects of play at work. I conducted an ethnographic study of the everyday practices of young IT professionals, revealing that workplace play has multiple instrumental aspects which are related to the temporality, spatiality, materiality and sociality of IT work practices.